SARS‐CoV‐2 vaccination response in patients with autoimmune hepatitis and autoimmune cholestatic liver disease. Issue 3 (15th March 2022) - Duengelhoef, Paul; Hartl, Johannes; Rüther, Darius; Steinmann, Silja; Brehm, Thomas T.; Weltzsch, Jan Philipp; Glaser, Fabian; Schaub, G. M.; Sterneck, Martina; Sebode, Marcial; Weiler‐Normann, Christina; Addo, Marylyn M.; et al.
Abstract: Background/Aims: In this observational study, we explored the humoral and cellular immune response to SARS‐CoV‐2 vaccination in patients with autoimmune hepatitis (AIH) and patients with cholestatic autoimmune liver disease (primary sclerosing cholangitis [PSC] and primary biliary cholangitis [PBC]). Methods: Anti‐SARS‐CoV‐2 antibody titers were determined using the DiaSorin LIAISON and Roche immunoassays in 103 AIH, 64 PSC, and 61 PBC patients and 95 healthy controls >14 days after the second COVID‐19 vaccination. The spike‐specific T‐cell response was assessed using an activation‐induced marker assay (AIM) in a subset of individuals. Results: Previous SARS‐CoV‐2 infection was frequently detected in AIH but not in PBC/PSC (10/112 (9%), versus 4/144 (2.7%), p = 0.03). In the remaining patients, seroconversion was measurable in 97% of AIH and 99% of PBC/PSC patients, respectively. However, in 13/94 AIH patients antibody levels were lower than in any healthy control, which contributed to lower antibody levels of the total AIH cohort when compared to PBC/PSC or controls (641 vs. 1020 vs. 1200 BAU/ml, respectively). Notably, antibody levels were comparably low in AIH patients with ( n = 85) and without immunosuppression ( n = 9). Also, antibody titers significantly declined within 7 months after the second vaccination. In the AIM assay of 20 AIH patients, a spike‐specific T‐cell response was undetectable in 45% despite a positive serology, while 87% (13/15) of the PBC/PSC demonstrated a spike‐specific T‐cell response. Conclusion: Patients with AIH show an increased SARS‐CoV‐2 infection rate as well as an impaired B‐ and T‐cell response to SARS‐CoV‐2 vaccine compared to PBC and PSC patients, even in the absence of immunosuppression. Thus, antibody responses to vaccination in AIH patients need to be monitored and early booster immunizations considered in low responders.